Ultrastrong gradient M50 bearing steel with lath-shape nano-martensite by ultrasonic shot peening and its enhanced wear resistance at elevated temperature - Yin, Fei; Han, Pengcheng; Han, Qingyou; Wang, Huihui; Hua, Lin; Cheng, Gary J (Materials & design, 2024)
[Display omitted] •Fabricated the ultrastrong gradient nano-martensite with thickness of 20 nm on M50.•Identified enhanced wear resistance of gradient nanostructured M50 at elevated temperature.•Analyzed the microstructure evolution of the gradient nanostructured M50.•Revealed the wear enhancement mechanisms of the gradient nanostructured M50. This investigation delves into the intricacies of the process mechanism for generating a gradient nanostructured surface (GNS) layer on M50 bearing steel, with the aim of augmenting its surface hardness and wear resistance under elevated temperature. The electron backscatter diffraction and transmission electron microscopy substantiate the successful formation of a GNS layer, surpassing 200 µm in thickness, on the M50 bearing steel treated by Ultrasonic shot peening (USP) technology. The severe plastic deformation (SPD) induced by the USP process resulted in a significant refinement of the martensite in M50 bearing steel, leading to a remarkable 32.25 % increase in surface hardness compared to its untreated coarse-grained (CG) counterpart. Pin-on-Disk wear tests were conducted at an elevated temperature of 300 °C on both the as-received CG-M50 and USP-treated M50 bearing steel samples to evaluate the impact of USP treatment on the wear resistance of M50 bearing steel. Experimental results reveal that the volume loss of the USP-treated M50 bearing steel is 94.9 % less than that of the untreated CG-M50 bearing steel after 4 h of wear tests. The improved wear resistance of the USP-treated M50 bearing steel can be attributed to the creation of an ultrastrong and stable GNS layer facilitated by USP.